Study of the Orthogonal Property of Recurrence Relations and the Differential Equation in Generalized Rodrigue’s Formula - Raj Kishor Sharma (International Journal of Mathematics And its Applications, 2014)
Let L_1 =L_1 (I) be the class of Lebesgue integrable functions on the interval I=[a,b], where 0 a < b < ∞ and let Γ(.) be the gamma function.